PENDAMPINGAN KEPADA SISWA SEKOLAH MENENGAH DI YOGYAKARTA DALAM PENERAPAN 5M SEBAGAI PERSIAPAN PEMBELAJARAN LURING - Dina Christin Ayuning Putri; Sri Hartati Yuliani; Rini Dwiastuti (Universitas Sanata Dharma, 2022)
The COVID-19 pandemic that has hit the whole world has affected various aspects of life, including education. Education during the pandemic is carried out online which has the potential to cause learning loss for students. Face-to-face learning is needed for students by considering all the risks. Preparation for offline learning is done by equipping students in implementing health protocols. This activity aims to equip students to be ready to carry out face-to-face learning by applying the ‘5M’ programs. Activities are carried out in the form of mentoring and discussion. The effectiveness of the activity was observed by comparing the pretest and posttest scores. The results show that the students' posttest scores are greater than the pretest scores, so it can be concluded that this activity is useful in adding students' knowledge of the ‘5M’ program as an effort to prevent COVID-19 transmission during face-to-face learning.